The prediction of mechanical performance of isotactic polypropylene on the basis of processing conditions. (28th January 2016) - Caelers, H.J.M.; Govaert, L.E.; Peters, G.W.M.
Abstract: A strategy is presented to predict the yield kinetics following from different thermomechanical histories experienced during processing in non-isothermal quiescent conditions. This strategy deals with three main parts, i.e. processing, structure and properties. In the first part the applied cooling conditions are combined with the crystallization kinetics and the cooling history of the material is calculated. From this history the lamellar thickness distributions are predicted in the second part. Finally, in the third part these distributions are used to predict yield stresses. Experimental validation is carried out for all the different parts of the strategy. In situ temperature measurements, lamellar thickness distributions from SAXS experiments and yield stresses measured in uniaxial tensile deformation are performed for validation purposes. The versatility is investigated by applying this procedure on two different iPP grades. The yield stress predictions show good agreement with the experimentally obtained results in two separate deformation mechanisms, and only a few parameters are dependent on the specific iPP grades that were used here. Moreover, it is shown that the average lamellar thickness is sufficient to predict the yield stress, and that the width of lamellar thickness distributions does not have to be taken into account. Graphical abstract: Highlights: A crystallization model is combined with the 1D-heat equation to predict spatial variable cooling history. Lamellar thickness is predicted from the cooling history using the Lauritzen Hoffman equation and experimentally validated. Yield stress predictions are made for samples prepared with different cooling rates, and compared to tensile test results. Similarities and differences between two iPP grades are identified and discussed. This work shows that the connection between processing and mechanical properties of semi-crystalline polymers is feasible.